Cases on interactive technology environments and transnational collaboration : concerns and perspectives - Mukerji, Siran; Tripathi, Purnendu (Hershey, PA : Information Science Reference, 2010)
"This book provides a comparative and comprehensive analysis of technologically enabled educational environments and various issues concerning education and collaborations across the world besides focusing on best practices and experiences from a varied range of countries"--Provided by publisher.
Keywords: Group work in education -- Computer networks -- Cross-cultural studies; Computer-assisted instruction -- Cross-cultural studies; Educational technology -- Cross-cultural studies; Education and globalization -- Cross-cultural studies